AN ANALYSIS OF "JIANG" SYLLABLE PRONOUNCIATION: A Case Study of Indonesian Students Learning Chinese - Xu, Wei (2023)
The problem studied in this paper is the pronunciation difficulties encountered by atonal native speakers when they learn tonal languages. The research method used in this paper is qualitative analysis. The purpose of this study is to compare and analyze the pronunciation difficulties encountered by Indonesian students whose mother tongue is Bahasa Indonesia (non-tonal language) when learning a second language (tonal language). The standard pronunciation corpus in this paper comes from the researcher. The researcher's Chinese has passed the Mandarin Chinese test and can be used as a standard sample of comparative analysis. The research object corpus comes from the students of the Chinese Department of the University of Banda Muria, Indonesia. The researchers selected a Chinese syllable - "jiang", and will collect a corpus of research subjects. This paper takes the "jiang" syllable as the research object, and investigates and studies the difficulties encountered by Indonesian-speaking students in learning the "jiang" syllable from four aspects: pronunciation, meaning identification, Chinese characters and context, and analyzes the difficulties the cause of.